Estimating the willingness to pay for reliable electricity supply: A choice experiment study - Ozbafli, Aygul; Jenkins, Glenn P. (Elsevier, 2016)
This research examines households' willingness to pay (WTP) for an improved electricity service. Households' stated WTP is estimated using the choice experiment (CE) method. The data used in the estimations come from 350 in-person interviews conducted during the period 5-22 August 2008 in North Cyprus. Compensating variation (CV) estimates for a zero-outage scenario are calculated using the parameter estimates from the mixed logit (ML) model; these are 6.65 YTL (Turkish lira) per month (3.02 USD) for summer and 25.83 YTL per month (11.74 USD) for winter. In order to avoid the cost of outages, households are willing to incur a 3.6% and a 13.9% increase in their monthly electricity bill for summer and winter, respectively. The WTP per hour unserved is 0.28 YTL (0.13 USD) for summer, and 1.08 YTL (0.49 USD) for winter. A preliminary cost-benefit analysis indicates that the annualized economic benefits are approximately 42.7 million YTL (19.4 million USD) for the residential sector. This would justify an investment in additional generation capacity of approximately 268 MW, which is far more than that which is needed to eliminate the service reliability problem. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Willingness to pay; Choice experiment; Electricity; Outages; Reliability